LQR-LMI control applied to convex-bounded domains. Issue 1 (1st January 2018) - da Ponte Caun, Rodrigo; Assunção, Edvaldo; Minhoto Teixeira, Marcelo Carvalho; da Ponte Caun, Alessandro
Abstract : Recently, propositions of new conditions necessary and sufficient in the controller's synthesis, based on linear quadratic problems, have been especially combined with the mathematical description in the form of Linear Matrix Inequalities (LMI), expanding its applications for continuous and uncertain systems in convex-bounded domains. In this class of studies, the Linear Quadratic Regulator provides a good relationship between performance and eigenvalues allocation, based on minimization of energy signals of the state and control variables. Thus, this work permits to get less conservative conditions in LMI control through the use of parameter-dependent Lyapunov functions in obtaining robust controllers under a certain decay rate. Illustratively, application examples evaluate the performance of the proposed theorems, whose validation addresses tests of feasibility subject to variation limit of the decay rate and the analysis of the temporal behavior of the interest signals.